Peningkatan Hasil Belajar PAI Dengan Menggunakan Media Pembelajaran Powerpoint di Kelas IV SD Negeri 1 Sijunjung - Putra, Toni Anda (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) for fourth-grade students at SDN 1 Sijunjung through the use of PowerPoint media. The study employs a Classroom Action Research (CAR) method consisting of four stages: planning, implementation, observation, and reflection. The research was conducted in two cycles, with each cycle completed in one meeting. The results reveal an improvement in students' learning outcomes from the pre-cycle to the second cycle. In the pre-cycle, the learning mastery level was only 45%, which increased to 60% in the first cycle and reached 70% in the second cycle. Although the students' learning outcomes did not fully meet the expected success indicators, this study demonstrates that the use of PowerPoint media has a positive impact on enhancing students' learning achievements. This research supports multimedia learning and constructivist theories, emphasizing the importance of visual media in improving the effectiveness of learning processes.